HUBUNGAN PERNIKAHAN DINI DENGAN KEJADIAN ANEMIA PADA KEHAMILAN - Z. Wahid, Rusna; Aksohini Wijayanti, Tut Rayani (NHM PRESS, 2024)
The incidence of anemia in pregnant women in Indonesia still receives serious attention from government. Based on data from the Central Statistics Agency, 48.9 percent of pregnant women are recorded experiencing anemia in 2024. One of the causes of anemia in pregnant women is age married and pregnant too young.2 This study aims to find out the relationship between Early Marriage with the Incidence of Anemia in Pregnant Women. The design of this study is an analytical survey. The approach used in this study is a cross sectional approach. The sample in this study is all pregnant women who registered in the KIA register book with a total of 117. The study showed that most of the respondents experienced early marriage (72.6%). In addition, most respondents also experienced anemia (73.5%). Result Bivariate analysis shows that there is a meaningful relationship between early marriage With the incidence of anemia in pregnant women with a P value of 0.000. The result of this study is that there is a relationship between early marriage and the occurrence of anemia in pregnant women